Peran Konten Edukatif Di Instagram Dalam Memotivasi Tugas Akhir Mahasiswa - Hanafiah, Anisa Nur; Wulandari, Yulianti Fajar; Himawan, Sultan (Prisani Cendekia Institute, 2024)
Educational content that can utilize its features such as Reels, Stories, Broadcast, Highlight successfully motivates students in completing their final assignments. Educational content is in accordance with the theory of the characteristics of new media presence markers, namely, interactivity that can increase engagement between students and account owners, demassification that allows the dissemination of relevant content to a wide audience, and asynchrony that provides flexibility of access for students. Although there are challenges such as time constraints and lack of direct interaction, educational content can still make a positive contribution in supporting student motivation and learning, seen from the positive response or response from students to the account owner. the availability of educational content on Instagram is included in extrinsic motivation, namely the availability of interesting learning resources, while the need for learning, support, information is included in intrinsic motivation. Social media including Instagram can be utilized as an effective educational tool because it fits the characteristics of new media to motivate students in their final project.